QuarkNet: A Unique and Transformative Physics Education Program - Marjorie Bardeen; Mitchell Wayne; M. Jean Young (MDPI AG, 2018)
The QuarkNet Collaboration has forged nontraditional relationships among particle physicists, high school teachers, and their students. QuarkNet centers are located at 50+ universities and labs across the United States and Puerto Rico. We provide professional development for teachers and create opportunities for teachers and students to engage in particle physics data investigations and join research teams. Students develop scientific knowledge and habits of mind by working alongside scientists to make sense of the world using authentic experimental data. Our program is based on a classroom vision where teaching strategies emulate closely the way scientists build knowledge through scientific and engineering practices. Program outcomes show that student engagement in research and masterclasses does develop an understanding of the process of scientific discovery and science. Teachers provide classroom environments that model scientific discovery and science practices and take advantage of opportunities to expand their involvement in the profession of science teaching. We describe success factors that enhance local center programs, and discuss important benefits of the program that flow on to the university faculty.